Civilization: the Dominant’s Ideology to Otherness - MEHDAOUI, Amaria (LANGUAGE ART, 2023)
Civilization, although an over-consumed notion used eagerly to differentiate societies’ ability to progress/not progress through time and space, taking into consideration internal and external features, challenges the post-colonial pursuit for transforming the colonial discourse into self-empowerment and its intention towards re-creation of the long-lost original identity. In an attempt to discuss the menace the term plays in entrapping the post-colonial consciousness into a game of otherness, this article views the concept of civilization as the dominant’s ideology towards the implementation of otherness as a doctrine. Otherness takes many forms; among them are the creation and the maintenance of different tools for defining the self in order to define the Rest as the Other. To explain this process, the researcher first sketches the history of the concept and its historical metamorphoses and then elucidates the importance behind its emergence after the Age of Enlightenment. The article subsequently reveals how civilization has been a colonial ideology all along, created and preserved through different discursive means, to shape the future of the post-colonial societies. Finally, the researcher proposes post-colonial civilizations to refer to those civilizations mingled not by geographical, religious, or cultural bounds but by sharing the experience of being subordinated by the one dominant civilization.